Thirty-Day Outcomes of Transcatheter Mitral Valve Replacement for Degenerated Mitral Bioprostheses (Valve-in-Valve), Failed Surgical Rings (Valve-in-Ring), and Native Valve With Severe Mitral Annular Calcification (Valve-in-Mitral Annular Calcification) in the United States: Data From the Society of Thoracic Surgeons/American College of Cardiology/Transcatheter Valve Therapy Registry - Guerrero, Mayra; Vemulapalli, Sreekanth; Xiang, Qun; Wang, Dee Dee; Eleid, Mackram; Cabalka, Allison K.; Sandhu, Gurpreet; Salinger, Michael; Russell, Hyde; Greenbaum, Adam; Kodali, Susheel; George, Isaac; et al. (Circulation. Cardiovascular interventions, 2020)
Transcatheter mitral valve replacement using aortic transcatheter heart valves has recently become an alternative for patients with degenerated mitral bioprostheses, failed surgical repairs with annuloplasty rings or severe mitral annular calcification who are poor surgical candidates. Outcomes of these procedures are collected in the Society of Thoracic Surgeons/American College of Cardiology/Transcatheter Valve Therapy Registry. A comprehensive analysis of mitral valve-in-valve (MViV), mitral valve-in-ring (MViR), and valve-in-mitral annular calcification (ViMAC) outcomes has not been performed. We sought to evaluate short-term outcomes of early experience with MViV, MViR, and ViMAC in the United States. Retrospective analysis of data from the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry. Nine hundred three high-risk patients (median Society of Thoracic Surgeons score 10%) underwent MViV (n=680), MViR (n=123), or ViMAC (n=100) between March 2013 and June 2017 at 172 hospitals. Median age was 75 years, 59.2% female. Technical and procedural success were higher in MViV. Left ventricular outflow tract obstruction occurred more frequently with ViMAC (ViMAC=10%, MViR=4.9%, MViV=0.7%; <0.001). In-hospital mortality (MViV=6.3%, MViR=9%, ViMAC=18%; =0.004) and 30-day mortality (MViV=8.1%, MViR=11.5%, ViMAC=21.8%; =0.003) were higher in ViMAC. At 30-day follow-up, median mean mitral valve gradient was 7 mm Hg, most patients (96.7%) had mitral regurgitation grade ≤1 (+) and were in New York Heart Association class I to II (81.7%). MViV using aortic balloon-expandable transcatheter heart valves is associated with a low complication rate, a 30-day mortality lower than predicted by the Society of Thoracic Surgeons score, and superior short-term outcomes than MViR and ViMAC. At 30 days, patients in all groups experienced improvement of symptoms, and valve performance remained stable. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT02245763.